Early Endoscopic Findings in Patients with Upper Gastrointestinal Bleeding in Bangladesh - Mallick, Uzzwal Kumar; Faruq, Mohammad Omar; Ishaque, SM; Ahsan, ASM Areef; Fatema, Kaniz; Ahmed, Fatema; Asaduzzaman, Mohammad; Shaikh, Md Merazul Islam; Mahfuzzaman, - (Bangladesh Critical Care Journal, 2015)
Objective: To determine etiological pattern of patients presenting with upper gastrointestinal bleeding in a tertiary care hospital of Bangladesh. Methods: This study was a prospective observational study, carried out in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2013 to June 2013. Fifty adult patients presenting with haematemesis and/or melaena admitted into gastroenterology inpatient unit from outpatient department or patients referred from other inpatient units of Department of Medicine of BSMMU were included in the study. Endoscopic examination was performed within 24 to 48 hours of presentation. Lower GI endoscopy was done in selected cases. Results: The study patients were predominantly young or of early middle age with mean age being 34.45 ± 16.5 yrs. A male preponderance was observed with male to female ratio being 7.3:1 (44 male and 6 female). 62% of the patients presented with both haematemesis and melaena, 26% with melaena only and 12% with haematemesis alone. Endoscopy of upper gastrointestinal tract demonstrated duodenal ulcer to be predominant finding (50%), followed by gastro-esophageal erosions (20%), gastric ulcer (12%), esophageal varices (10%), gastric adenocarcinoma (4%) and stomal ulcer (4%). Conclusions: Endoscopy revealed that duodenal ulcer was the most common cause of upper gastrointestinal bleeding followed by oesophageal erosion, gastric ulcer, esophageal varices and stomal ulcer. Peptic ulcer disease still remains as the major cause of acute upper gastrointestinal haemorrhage, though cases of oesophageal erosion were also significant. Bangladesh Crit Care J September 2015; 3 (2): 60-62